2015
DOI: 10.1021/acs.energyfuels.5b01287
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Group Type Separation of Gas Oil Resins by High Performance Liquid Chromatography on Hyper-Cross-Linked Polystyrene Stationary Phase

Abstract: An analytical method that provides chromatographic information regarding gas oil resins has been developed. This method uses a high performance liquid chromatographic system without backflushing and a single hyper-cross-linked polystyrene column. The use of the latter was warranted as it retains aromatic model compounds more effectively than a typically used silica-based amino-cyano column. Moreover, there was no need for extra solvent drying techniques because a retention time reproducibility of 2.9% RSD over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In recent years, monodisperse polymer nano/microspheres have attracted remarkable research interest because of their versatile applications, such as chromatographic separation, medical immunization, and bioengineering . Due to their great potential, many effective polymerization techniques have been developed for preparing polymer particles with small size, narrow size distribution, good sphericity, and varying composition .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, monodisperse polymer nano/microspheres have attracted remarkable research interest because of their versatile applications, such as chromatographic separation, medical immunization, and bioengineering . Due to their great potential, many effective polymerization techniques have been developed for preparing polymer particles with small size, narrow size distribution, good sphericity, and varying composition .…”
Section: Introductionmentioning
confidence: 99%
“…The ions in the CHN 1 class are present in all the chromatographic fractions, indicating that this class may consist of species with different functional groups which experience different retention mechanisms. This corresponds to literature where different N-containing compounds in gas oil (distillation fraction of crude oil with boiling point range of 204–524 °C) were separated/fractionated with normal phase HPLC …”
Section: Resultsmentioning
confidence: 97%
“…For the positive ion mass spectra, the chromatographic fractions (Figure 3a) are dominated by the CHN 1 class, which were separated/fractionated with normal phase HPLC. 37 The other (less prominent) classes reveal interesting characteristics of the chromatographic separation. The CHO 2 class was less retained than the CHO 1 class.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…The authors identified some stability issues with the stationary phase, indicating that more study was needed to make this separation applicable to a higher-throughput scenario. A hypercrosslinked polystyrene stationary phase and UV detection was used to perform a group-type separation of gas oil resins, which showed that, with a quaternary solvent gradient, this phase was capable of separating model nitrogen compounds into two chromatographic regions that were distinct from aromatics . This stationary phase was later shown to retain analytes with primarily a π–π electron interaction, enabling separations that are similar to charge-transfer phases .…”
Section: Separations By Target Analytementioning
confidence: 99%
“…A hypercrosslinked polystyrene stationary phase and UV detection was used to perform a group-type separation of gas oil resins, which showed that, with a quaternary solvent gradient, this phase was capable of separating model nitrogen compounds into two chromatographic regions that were distinct from aromatics. 63 This stationary phase was later shown to retain analytes with primarily a π−π electron interaction, enabling separations that are similar to charge-transfer phases. 33 Gas oil resins were separated into seven regions, allowing for qualitative comparison of samples, although the use of higher carbon-number standards or fraction analysis may have provided more insight into the composition of these regions.…”
Section: Separation Sciencementioning
confidence: 99%